The impact of a standardized order set for the management of non-hip fragility fractures in a Fracture Liaison Service. Issue 12 (December 2016) - Senay, A.; Delisle, J.; Giroux, M.; Laflamme, G.; Leduc, S.; Malo, M.; Nguyen, H.; Ranger, P.; Fernandes, J.
Abstract Summary We analysed the impact of a standardized order set empowering staff nurses to independently manage a Fracture Liaison Service over a 9-month period. Nurses identified between 30 and 70 % of non-hip fragility fractures to the unit in charge of management over time. The latter managed 58 % of referred patients. Introduction The main goal of this study was to evaluate the impact of a standardized order set empowering nurses to independently manage a fracture liaison service (FLS). Methods Since November 2014, an order set allowed nurses of a Montreal hospital, Quebec, Canada to entirely manage an FLS on their own. Nurses followed an 6-h training program on-site. Emergency department (ED) and orthopaedic outpatient clinic (OC) nurses identified non-hip fragility fractures. Medical day treatment unit (MDTU) nurses were in charge of the management (investigation and treatment initiation). The list of patients, 50 years and older, with a fracture were retrieved for the period of November 2014 to July 2015. Performance was assessed with the rate of identification over time and the rate of management of non-hip fragility fractures. Results Over the 9-month period, 346 patients of ≥50 years old were seen for a fracture, of which 190 met fragility criteria (excluding hip fractures). A sinusoid pattern of rates of identification between 30-70 % was observed over time. An average proportion of 58.1 % of fracture patients were managed by MDTU nurses. Conclusions A standardized order set legally allowing nurses to manage an FLS led to identification rates varying from 30–70 % and a management rate close to 60 % for referred patients over a 9-month period, which largely exceeds that of standard care. Identification was mostly compromised by difficulty integrating the order set into routine practice. Enforcement of the hospital policy on fragility fractures could help yield efficiency of identification of osteoporosis-related fractures by the staff.